2020
DOI: 10.32615/ps.2020.030
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological study of SiK impact on Castanea sativa Mill. tolerance to drought stress

Abstract: Drought is an abiotic stress that may be aggravated by climate changes with increasingly warmer and drier summers. This is a severe problem in the chestnut crop in Portugal due to its need for water during this time, which is essential for good formation and development of the fruit. Si fertilization is referenced by several authors as important in the tolerance of plants under drought. The experiments were carried out in the field trial and chestnuts were fertilized with 0, 5, 7.5, and 10 mM potassium silicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
(39 reference statements)
2
3
0
Order By: Relevance
“…Relative to the membrane injury, the present study also showed a significant decrease in ROS in Si-treated chestnut plants under abiotic stress conditions similar to previous studies ( Carneiro-Carvalho et al., 2020 ; Carneiro-Carvalho et al., 2021 ). In this study, oxidative damage was significantly reduced in C. sativa plants under water stress.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Relative to the membrane injury, the present study also showed a significant decrease in ROS in Si-treated chestnut plants under abiotic stress conditions similar to previous studies ( Carneiro-Carvalho et al., 2020 ; Carneiro-Carvalho et al., 2021 ). In this study, oxidative damage was significantly reduced in C. sativa plants under water stress.…”
Section: Discussionsupporting
confidence: 91%
“…The data show that Si fertilization significantly increased the accumulation of SS concentration in plants exposed to NIP by approximately 120% in 2015 (Figure 3A) and by 180% in 2016 (Figure 3B), between the 0-and 10-mM SiK ® treatments, as previously observed by other authors in chestnut plants (Carneiro-Carvalho et al, 2020;Carneiro-Carvalho et al, 2021). When examining the IP, a similar tendency was observed.…”
Section: Soluble Sugars and Starchsupporting
confidence: 87%
See 2 more Smart Citations
“…Although there have been some studies on the use of foliar applications of Si to fruit trees, their focus was on yield and fruit quality (Artyszak 2018), and there is very limited research on the role of foliarly applied Si on water relations and gas exchange. A study on water-stressed chestnut trees fertilized with Si (Carneiro-Carvalho et al 2020) suggested that foliarly applied Si can reduce cuticular transpiration and permeability to water vapor, limiting the loss of water and, thus, promoting better tree water status, although they used a combination of soil-applied and foliarly applied Si.…”
Section: Discussionmentioning
confidence: 99%